Automatic Detection of Fiducial Landmarks Toward the Development of an Application for Digitizing the Locations of EEG Electrodes: Occipital Structure Sensor-Based Work - Gallego Martínez, Elieser E.; González Mitjans, Anisleidy; Garea-Llano, Eduardo; Bringas-Vega, Maria L.; Valdes-Sosa, Pedro A. (Frontiers in Neuroscience, 2021)
The electrophysiological source imagine reconstruction is sensitive to the head model construction, which depends on the accuracy of the anatomical landmarks location knowns as fiducials. This work describes how to perform automatic fiducials detection, towards development of an application for automatic electrodes placement (digitization), over a three dimensional surface of a subject head, scanned with the Occipital Inc. structure sensor ST01. We offer a wide description of the proposed algorithm to explore the three dimensional object unto features detection, by means of: dimensional reduction with perspective projection from 3D to 2D, object detection with custom detectors, robotic control of mouse motion and clicks events and re-projection from 2D to 3D to get spatial coordinates. This is done taking into account the characteristics of the scanner information, the training process of detectors with Computer-Vision Toolbox resources of MATLAB® R2018b, the integration of FieldTrip Toolbox and the main properties of several ways to represents pixels; putting together all those things to automatically find the fiducials landmarks to generate the subject coordinate system. All this results are presented as the initial state of a project focused on development of an application for automatic electrode digitization.